2014
DOI: 10.1016/j.bbabio.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing photosynthetic efficiency and culture productivity in cyanobacteria upon minimizing the phycobilisome light-harvesting antenna size

Abstract: A phycocyanin-deletion mutant of Synechocystis (cyanobacteria) was generated upon replacement of the CPC-operon with a kanamycin resistance cassette. The Δcpc transformant strains (Δcpc) exhibited a green phenotype, compared to the blue-green of the wild type (WT), lacked the distinct phycocyanin absorbance at 625nm, and had a lower Chl per cell content and a lower PSI/PSII reaction center ratio compared to the WT. Molecular and genetic analyses showed replacement of all WT copies of the Synechocystis DNA with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
170
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(183 citation statements)
references
References 55 publications
11
170
0
2
Order By: Relevance
“…In PCC 7002, the cpcBACDEF operon encodes the major components of the peripheral rods including the α-(CpcA) and β-subunits (CpcB) of phycocyanin, the rod linkers (CpcC and CpcD), and two proteins involved in attachment of the phycocyanobilin pigment to the α-phycocyanin subunit (CpcE and CpcF) (Bryant et al, 1990). Since reduction of antennae size has been a promising strategy for increasing light penetration into high-density cyanobacterial cultures (Kirst et al, 2014), we designed an sgRNA to target cpcB and inhibit transcription of the entire cpcBACDEF operon. Others have shown that when the rod proteins are deleted there is a decrease in absorbance corresponding to phycocyanin at 635 nm (Lea-Smith et al, 2014).…”
Section: 3 Results and Discussionmentioning
confidence: 99%
“…In PCC 7002, the cpcBACDEF operon encodes the major components of the peripheral rods including the α-(CpcA) and β-subunits (CpcB) of phycocyanin, the rod linkers (CpcC and CpcD), and two proteins involved in attachment of the phycocyanobilin pigment to the α-phycocyanin subunit (CpcE and CpcF) (Bryant et al, 1990). Since reduction of antennae size has been a promising strategy for increasing light penetration into high-density cyanobacterial cultures (Kirst et al, 2014), we designed an sgRNA to target cpcB and inhibit transcription of the entire cpcBACDEF operon. Others have shown that when the rod proteins are deleted there is a decrease in absorbance corresponding to phycocyanin at 635 nm (Lea-Smith et al, 2014).…”
Section: 3 Results and Discussionmentioning
confidence: 99%
“…The leaves of yls mutant plants were yellow-green at the seedling stage but became progressively greener as they matured, indicating that another mechanism can compensate for the loss of the cpSRP54 pathway during the later developmental stage. One interpretation is that cpSRP43 can function independently of cpSRP54, to accomplish the thylakoid membrane assembly process (Yu et al 2012;Kirst et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…If plants had fewer light-harvesting pigments (e.g., chlorophylls and carotenoids) per photosystem (10) and fewer photosystems in their uppermost leaves, light might be absorbed more judiciously, and a greater proportion of absorbed photons converted to biomass. This avenue has been pursued for some years in algae and cyanobacteria, often with notable success (20,21), but not yet convincingly in crop plants. Lowering leaf absorptivity remains a significant opportunity for improving crop yield (10) although it is worth noting that such highly efficient plants might be at a disadvantage under some conditions, compared with normally pigmented competitors, and could require careful plant husbandry to realize their increased yield.…”
Section: Targets Of Opportunitymentioning
confidence: 99%